Chinese capital flows to African economies and real bilateral exchange rates - Coletta Frenzel Baudisch (Philipps-University Marburg, School of Business and Economics, 2019)
Since the turn of the millennium, China opened up internationally both in terms of its current account (trade) and its capital account, even though the opening of the latter happened de facto, not de jure. With respect to China being Africa's largest trading partner and developing investor in combination with its desire for African natural resources, we embark on an analysis of the impact of several categories of Chinese capital flows to African economies on the bilateral real exchange rate. We conduct a panel data analysis by means of a Hausman-Taylor-estimation over the period 2003-2016. Our results suggest that capital flows from China to Africa in the form of mainly economic cooperation projects, but also FDI contribute to an appreciation of the local currencies vis à vis the RMB, while no such effect appears for aid ows from China. The former two categories may pose a risk of Dutch Disease effects. Since many African countries have pegged their currencies to the Euro, and the Renminbi abandoned its peg to the US Dollar over the sample period, valuation effects of capital ows must be interpreted in this context.
Keywords: F19; F21; F35; F62; 330; real bilateral exchange rates; FDI; economic cooperation; aid; trade; Sino-African economic relations